Redescription and phylogenetic analyses of Thaparocleidus gomtius and T. sudhakari (Monogenea: Dactylogyridae) from Wallago attu (Siluriformes: Siluridae) in India - Verma C.; Chaudhary A.; Singh H. S. (Helminthologia, 2017)
Two species of Thaparocleidus Jain (1952a) were found harboring W. attu from the Ganga River at two localities, Meerut and Farrukhabad, Uttar Pradesh, India, during the period of 2013-2015. Morphology and morphometric study of specimens identified as Thaparocleidus gomtius (Jain, 1952a) Lim, 1996 and T. sudhakari (Gusev, 1976) Lim, 1996. Molecular analyses using the 18S rRNA gene confirmed the validity of T. gomtius and T. sudhakari and demonstrated that both the species clustered with other Thaparocleidus species from different geographical regions. We aim at reassessing the taxonomy and establishing the phylogenetic relationships among these two redescribed species with other representatives of the genus Thaparocleidus.